1999
DOI: 10.1080/00797308.1999.11822494
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a Boy with Atypical Ego Development

Abstract: A multifaceted mode of therapeutic action is delineated as the complex neuropsychological and psychogenic factors in the development and functioning of an unusual four-year-old boy became elucidated. In addition to standard technique, the author developed a variety of psychoanalytically informed ways to facilitate his growth and ameliorate deviational aspects, especially his difficulties in appreciating and responding to the social-emotional world and establishing stable, integrated mental representations of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…[p. 37] This tendency appears even in the work of Fonagy and his colleagues, who noted the crucial importance of developmental interventions in successful analyses at the Anna Freud Centre (Fonagy and Target 1996b), and yet, in the same year, felt the need to distinguish genuine child analysis involving interpretation of conflict from psychodynamic developmental therapy (Fonagy and Target 1996a). This distinction between the child analyst's functioning as a developmental object and as a provider of insight continues to occur in our literature (e.g., Olesker 1999;Schmuckler 1999b;Yanof 1996). For example, helping a child to lower his or her stimulation level, to identify and delineate affects in order to encourage affect regulation, and to remember repressed affects become defined as developmental help.…”
Section: The Facilitation Of Insightfulnessmentioning
confidence: 95%
See 2 more Smart Citations
“…[p. 37] This tendency appears even in the work of Fonagy and his colleagues, who noted the crucial importance of developmental interventions in successful analyses at the Anna Freud Centre (Fonagy and Target 1996b), and yet, in the same year, felt the need to distinguish genuine child analysis involving interpretation of conflict from psychodynamic developmental therapy (Fonagy and Target 1996a). This distinction between the child analyst's functioning as a developmental object and as a provider of insight continues to occur in our literature (e.g., Olesker 1999;Schmuckler 1999b;Yanof 1996). For example, helping a child to lower his or her stimulation level, to identify and delineate affects in order to encourage affect regulation, and to remember repressed affects become defined as developmental help.…”
Section: The Facilitation Of Insightfulnessmentioning
confidence: 95%
“…In general, most child analysts continue to stress the importance of insight in leading to structural change and removing the obstacles to developmental momentum, held to be the goals of child analysis. To be sure, in the analytic treatment of children, we are well aware of the child analyst's role as a developmental object (Sandler Kennedy, and Tyson 1980;Scharfman 1971;Sugarman, in press), as well as the need to provide developmental help (Fonagy and Target 1996a;Greenspan 1997;Hurry 1998;Olesker 1999;Yanof 1996). And there has even been a suggestion in the child analytic literature that insight is not crucial to the mutative impact of child analysis (Cohen and Solnit 1993;Scott 1998).…”
Section: The Role Of Insightmentioning
confidence: 99%
See 1 more Smart Citation
“…Some psychodynamic therapists, however, have refused to throw the proverbial baby out with the bathwater, continuing to apply psychodynamic interventions in the treatment of the disorder. There is a modest but growing number of published case studies of successful psychoanalytic treatment of adults (Polmear, 2004) and children (Olesker, 1999;Bromfield, 2000;Pozzi, 2003;Cassidy, 2004;Shulman, 2004;Topel and Lachmann, 2008) with a diagnosis of Asperger's disorder. It has been suggested that Asperger's disorder in children shares some similarities with narcissistic personality disorder in adults and thus can be subjected to psychoanalytic intervention (Shuttleworth, 1999).…”
mentioning
confidence: 98%
“…Oleskar refers to the building of the affective underpinnings of her patient's cognition by the phrase "social affective scaffolding" (25, p. 40). What links these two case presentations by Bromfield and Oleskar (24,25) is the therapists'ability to develop a "common language" to communicate with their pervasive developmentally disordered patients, children for whom social communication, even if language is present, is basically deviant. (Another psychoanalyst, Paulina Kernberg [27], reaches a similar conclusion in her work with psychotic and autistic patients using an object relations theory approach.…”
Section: Casementioning
confidence: 99%